Convergencia de la normativa de contabilidad gubernamental a NICSP aplicados al GAD Provincial de los Ríos periodo 2020 - Cruz Vergara, Victor Medardo (2020)
El Gobierno Autónomo Descentralizado de la Provincial de Los Ríos is a public entity with political, administrative and financial independence that is in charge of manifesting and preparing plans in order to guarantee the development of the Province and the country, it has trained and effective personnel, To carry out various assigned activities, it carries out processes aimed at achieving total satisfaction of the requirements and needs of users, as well as achieving its objectives and fulfilling as a public entity. In order to carry out this case study research, agreements, laws, regulations and regulations that currently exist have been taken into account, exposed by organizations aimed at convergence to the International Public Sector Accounting Standards. The IPSAS are designed for their application in financial entities in the Public Sector and contribute to adequate decision-making, improving the quality and reliability of financial reports and allowing comparability and understanding in the users who have access to this information. The Government of Los Ríos will have mandatory compliance with the presentation of the schemes defined by the Ministry of Economy and Finance applying the International Public Sector Accounting Standards and for this the financial area specifically the accounting unit will have to assume responsibility, that is why our The main problem is based on the execution of the application of this regulation and they will be in charge of the registration, classification and accounting.